Cost-effectiveness of empagliflozin for the treatment of heart failure with reduced ejection fraction in China - Sang, Haiqiang; Wan, Yiming; Ma, Zhenzhou; Zhang, Shengye; Zhao, Qiuping (Frontiers in Cardiovascular Medicine, 2022)
Aim To determine the pharmacoeconomics of empagliflozin for the treatment of heart failure (HF) with reduced ejection fraction in China and to provide evidence-based reference for clinical rational drug selection and medical decision-making. Research design and methods We used the Markov model to evaluate the cost-effectiveness of empagliflozin for the treatment of HF with reduced ejection fraction (HFrEF). We evaluated the cost-effectiveness of the standard treatment in addition to empagliflozin (empagliflozin group) vs. the cost-effectiveness of the standard treatment alone (standard treatment group). Results We found that each additional quality-adjusted life year (QALY) in the empagliflozin group costed 3,842.20 more, which was less than China’s gross domestic product (GDP) per capita in 2021 (11,981). The steady-state mortality in the two groups was the key factor affecting the incremental cost-effectiveness ratio (ICER). Probabilistic sensitivity analysis revealed that when the willingness-to-pay (WTP) threshold was one time the GDP per capita in 2021 (11,981) and three times the GDP per capita in 2021 (35,943), the probability of the empagliflozin group being cost-effective was 85.8 and 91.6%, respectively. Conclusion Compared with the standard treatment alone, the addition of empagliflozin to the standard treatment was more cost-effective for the treatment of HFrEF in China.